2017
DOI: 10.18632/oncotarget.21888
|View full text |Cite
|
Sign up to set email alerts
|

A missense variant in EZH2 is associated with colorectal cancer risk in a Chinese population

Abstract: Colorectal cancer (CRC) ranks the fifth leading cause of cancer death in China. EZH2 is a member of Polycomb-group (PcG) family and associated with transcriptional repression and cancer development. In this study, we report the association between a missense variant in EZH2 and risk of CRC. Through a systematic selection of variants in EZH2, we identified rs2302427 in the exon region of EZH2 and genotyped this variant in 852 CRC patients and 1,303 healthy controls using Taqman genotyping assay. The association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The EZH2 SNP, rs2302427, encodes the Ezh2 D185H substitution, which is located in the domain that interacts with DNA methyltransferases ( Table S2 ). This SNP has been identified as a risk factor for colorectal cancer in a Chinese population [ 51 ]. This SNP was also detected in an AML patient with a morphology resembling acute promyelocytic leukemia without the PARA gene rearrangement [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The EZH2 SNP, rs2302427, encodes the Ezh2 D185H substitution, which is located in the domain that interacts with DNA methyltransferases ( Table S2 ). This SNP has been identified as a risk factor for colorectal cancer in a Chinese population [ 51 ]. This SNP was also detected in an AML patient with a morphology resembling acute promyelocytic leukemia without the PARA gene rearrangement [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an association between a missense variant in EZH2 and risk of CRC was discovered by the Li group. They identified that the presence of the rs2302427 variant showed a significant association with increased CRC susceptibility [103]. Recent studies point to other mechanistic roles of HKMTs in CRC.…”
Section: The Role Of Major Epigenetic Enzymes In Crc and Therapeutic ...mentioning
confidence: 99%